2021
DOI: 10.2147/jir.s327329
|View full text |Cite
|
Sign up to set email alerts
|

β-Nicotinamide Mononucleotide (NMN) Administrated by Intraperitoneal Injection Mediates Protection Against UVB-Induced Skin Damage in Mice

Abstract: Ultraviolet light is an important environmental factor that induces skin oxidation, inflammation, and other diseases. Nicotinamide mononucleotide (NMN) has the effect of antioxidation and improving various physiological processes. This study explores the protective effect of NMN monomers given via intraperitoneal injection on UVB-induced photodamage. Methods:We used a murine model of UVB-induced photodamage to evaluate the effect of an NMN monomer on photoaging skin by assessing skin and liver tissue sections,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 82 publications
2
9
1
Order By: Relevance
“…45 In addition, D-gal treated cells showed upregulated gene expression of pro-inflammatory factors such as IL-1β, IL-6, and TNF-α, and cellular senescence associated genes P53 and P21. 46 In the present study, the cellular transcriptome demonstrated that D-gal up-regulated the gene expression of IL6ST, IL-1A, and NF-κB1, which have been identified as SASPs in the intestine of old rats. 47 Treatment of 500 μM NMN down-regulated these inflammatory SASPs in D-gal treated IPEC-J2 cells.…”
Section: Food and Function Papersupporting
confidence: 54%
See 1 more Smart Citation
“…45 In addition, D-gal treated cells showed upregulated gene expression of pro-inflammatory factors such as IL-1β, IL-6, and TNF-α, and cellular senescence associated genes P53 and P21. 46 In the present study, the cellular transcriptome demonstrated that D-gal up-regulated the gene expression of IL6ST, IL-1A, and NF-κB1, which have been identified as SASPs in the intestine of old rats. 47 Treatment of 500 μM NMN down-regulated these inflammatory SASPs in D-gal treated IPEC-J2 cells.…”
Section: Food and Function Papersupporting
confidence: 54%
“…Previously, a study also reported the enhancing effect of NMN treatment on the antioxidant capacity. 46 Han and his colleagues have investigated the supplementary effects of different doses of d -gal ranging from 5–20 g kg −1 on weaned piglets. 48 The results showed that d -gal did not cause a significant change in serum SOD, but a specific dose-dependent increase in the GSH-Px activity and MDA content and a decrease in the CAT activity were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo studies of NMN treatment are administered mainly by oral gavage and intraperitoneal injection. Zhou et al demonstrated that both types of administration of NMN protect against UVBinduced skin damage in mice [23]. Contrary, NMN supplementation in the medium did not up-regulate NAD + levels directly in our study.…”
Section: Discussioncontrasting
confidence: 92%
“…A cascade of reactions is triggered after UV exposure, with ROS triggering inducing the release of IL-6, IL-1β, and TNF-α ( Zhou et al, 2021 ). ELISA kits were used to determine IL-6, IL-1β, and TNF-α expression in the rat skin tissue homogenate.…”
Section: Resultsmentioning
confidence: 99%
“…MMPs degrade collagen and elastin in the extracellular matrix in vivo . MMP-1 breaks down intact type I and III fibrillar collagen, ultimately leading to progressive senescence of fibroblasts ( Rui-Zhen et al, 2004 ; Zhang and Tian, 2007 ; Zhou et al, 2021 ). Additionally, MMP-1 upregulates the expression of IL-6, IL-1β, and TNF-α by activating nuclear factor-κB (NF-κB), which can lead to the inflammatory infiltration of neutrophils and further production of ROS ( Xiao et al, 2016 ; Ighodaro and Akinloye, 2018 ).…”
Section: Introductionmentioning
confidence: 99%